TEKNOLOGI PENGOLAHAN LIMBAH KOTORAN SAPI MENJADI PUPUK ORGANIK DI NAGARI LINGKUANG AUA KABUPATEN PASAMAN BARAT - Ferry Lismanto Syaiful; Ferian Rifaldy (Jurnal Hilirisasi IPTEKS, 2020)
The people in Lingkuang Aua village make their living in agriculture, plantation, and animal husbandry. However, the people in this Nagari have not optimized the village's potential, especially in the field of animal husbandry, including livestock manure waste. Animal manure has the potential to be processed as organic fertilizer. Fertilizer is a commodity that is needed in the agricultural and plantation sectors. In Lingkuang Aur village, the use of chemical fertilizers is still high in the West Pasaman area. However, the price of chemical fertilizers is costly, and even excessive use can damage soil fertility. Organic fertilizers are fertilizers derived from crop residues and livestock manure that have undergone a decomposition/weathering process. The advantages of this fertilizer are environmentally friendly, increase soil fertility, and increase farmers' income. This activity aims to provide knowledge and understanding for farmers in processing livestock manure into organic fertilizer. The methods used are socialization, demonstration/training, and evaluation. The targets of the activity are breeders and the community in Nagari Lingkuang Aur. This activity provides a technology package for making organic fertilizers based on cow dung and EM4, as well as the addition of organic matter found in this village. The result of this activity is that breeders and the community have increased their knowledge and understanding of processing livestock manure into organic fertilizer. The use of organic fertilizers can increase soil fertility, and the price is low, which provides benefits for farmers/breeders. It is hoped that farmers and breeders can apply organic fertilizers to agricultural land to reduce the high price of fertilizers.